Graphene Oxide Improves in vitro Fertilization in Mice With No Impact on Embryo Development and Preserves the Membrane Microdomains Architecture - Bernabò, Nicola; Valbonetti, Luca; Raspa, Marcello; Fontana, Antonella; Palestini, Paola; Botto, Laura; Paoletti, Renata; Fray, Martin; Allen, Susan; Machado-Simoes, Juliana; Ramal-Sanchez, Marina; Pilato, Serena; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
During the latest years, human infertility worsened all over the world and is nowadays reputed as a global public health issue. As a consequence, the adoption of Assisted Reproductive Technologies (ARTs) such as In Vitro Fertilization (IVF) is undergoing an impressive increase. In this context, one of the most promising strategies is the innovative adoption of extra-physiological materials for advanced sperm preparation methods. Here, by using a murine model, the addition of Graphene Oxide (GO) at a specific concentration has demonstrated to increase the spermatozoa fertilizing ability in an IVF assay, finding that 0.5 μg/mL GO addition to sperm suspensions before IVF is able to increase both the number of fertilized oocytes and embryos created with a healthy offspring given by Embryo Transplantation (ET). In addition, GO treatment has been found more effective than that carried out with methyl-β-cyclodextrin, which represents the gold standard in promoting in vitro fertility of mice spermatozoa. Subsequent biochemical characterization of its interaction with male gametes has been additionally performed. As a result, it was found that GO exerts its positive effect by extracting cholesterol from membranes, without affecting the integrity of microdomains and thus preserving the sperm functions. In conclusion, GO improves IVF outcomes in vitro and in vivo, defining new perspectives for innovative strategies in the treatment of human infertility.